Udder defense system: Effect of milk SCC level on Th1/Th2 cytokine balance - Safak, Tarik; Risvanli, Ali (Journal of the Hellenic Veterinary Medical Society, 2022)
The immune system of the cow is kept strong to protect the cows from mastitis, which causes economic losses for dairy cattle herds. Cellular immunity, especially, plays an important role as a first-line defense system. In the case of inflammation, cytokines play a decisive role in monitoring this process. In this study, the relationship between somatic cell count (SCC) and cytokine (tumor necrosis factor alpha, interferon gamma, and interleukins [TNF-α, IFN-γ, IL-2, -4, -5, and -10, respectively]) concentrations in milk were determined. It was decided to support the humoral and cellular aspects of the udder defense system by determining the T-helper cell (Th1/Th2) cytokine polarization in high SCC milk from cows with signs of mastitis. Milk samples from 180 cows were divided into five groups according to the somatic cell count level (˂ 150 x 103, 151 x 103–400 x 103, 401 x 103–600x103, 601 x 103–1,000 x 103, and > 1,000x103 cells⁄mL). It was understood that the Th1 direction was determined before mastitis was formed, that is when SCC was low (˂ 150 x 103). As a result, it was concluded that theTh1 polarization should be supported to protect cows from mastitis.